2002
DOI: 10.1007/s00423-002-0291-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbidity on the overall survival and the cause of death in patients after colorectal cancer resection

Abstract: Standardized comorbidity should be considered as a factor in survival studies of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 30 publications
3
23
1
4
Order By: Relevance
“…Comorbidity has proven to be difficult to define and measure accurately [20,22]. However, as measured by the well-validated and extensively applied CCI, comorbidity has been shown to be an independent predictor of outcome (although with the association in the opposite direction to that in our study) in previous studies [25,29,34,35].…”
Section: Original Articlecontrasting
confidence: 53%
See 3 more Smart Citations
“…Comorbidity has proven to be difficult to define and measure accurately [20,22]. However, as measured by the well-validated and extensively applied CCI, comorbidity has been shown to be an independent predictor of outcome (although with the association in the opposite direction to that in our study) in previous studies [25,29,34,35].…”
Section: Original Articlecontrasting
confidence: 53%
“…This was, therefore, a homogenous population in terms of overall health status that would make it more difficult to show an effect of comorbidity. In the analysis by Rieker et al [25], two-thirds of patients had CCI scores between 0 and 2 while one-third of patients had scores of >2. They showed that greater comorbidity was significantly correlated with shorter OS in patients who had undergone resection of colorectal cancer [25].…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…의 지표가 개발 및 적용되고 있으며,(7-9) 위암, (7,8) 유방암, (10)(11)(12)(13)(14)(15), 폐암, (11,16,17) 대장암, (6,11,18) 전립선암,(11) 방광암, (19) 및 신장암 (20) Table 3). CCI=Charlson Comorbidity Index; CI=confidence interval.…”
Section: 환자의 동반상병을 종합적으로 평가하기 위해 최근까지 여러 종류unclassified